Analisis Profil Guru Matematika dalam Membangun Konsep Diri Siswa - Yuliyanti Yuliyanti; Widodo Winarso; Muhamad Ali Misri (Universitas Asahan, 2019)
This study aims to analyze the profile of SMPN 1 Lemahabang mathematics teacher implicating or not in developing self-concept of students and how much influence the profile of SMPN 1 Lemahabang teacher in developing self-concept of students. This research is a quantitative study using the One ShotCase Study design, the sampling technique used was purposive sampling and a sample of 5 mathematics teachers and 178 students of Lemahabang Middle School was selected. The research method used is the teacher performance appraisal (PKG) and questionnaire/questionnaire. The results of this study indicate that: (1) the profile of mathematics teachers according to the results of teacher performance evaluations has an average value of 85.43% which falls into the good category. Strengthened by the mathematics teacher's profile according to student perceptions of an average score of 73.86% which is included in the medium category (2) students' self-concept has an average value of 65.23% which is included in the medium category (3) based on Data analysis shows that the mathematics teacher's profile has implications in building students' self-concepts. This can be seen from the price of t count = -0.836 with a significance value of -0.836 <0.05, so Ho is rejected and Ha is accepted, which means that there are implications for the teacher's profile in developing students' self-concept